UMP lecturers produce reusable face shields for medical frontliners - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2020)
KUANTAN: High demand of face shields by frontliners battling the Covid-19 infection has prompted three Universiti Malaysia Pahang (UMP) lecturers to produce their very own 3D-printed face shields.